The Effect Of Palm Oil Exports, Machinery Imports, And Foreign Debt On Foreign Exchange Reserves In Indonesia 2005–2024 - Kautsar Fatin Dharmawan Nasution; Armin Rahmansyah Nasution (Economic Education Analysis Journal, 2026)
This study examines the influence of crude palm oil (CPO) exports, machinery imports, and external debt on Indonesia’s foreign exchange reserves during the 2005–2024 period amid fluctuating global economic conditions. Using a quantitative explanatory approach, this research analyzes the short-run and long-run relationships between external sector variables and foreign exchange reserve stability in Indonesia. Secondary time-series data were obtained from Bank Indonesia and the Central Statistics Agency, then analyzed using the Error Correction Model (ECM). The findings reveal that CPO exports have a negative but insignificant effect on foreign exchange reserves in both the short and long run, indicating that export earnings are not fully accumulated as reserve assets. Machinery imports show a positive but insignificant effect in the short run, while exerting a positive and significant effect in the long run through increased industrial productivity and export capacity. External debt positively and significantly affects foreign exchange reserves in both periods through foreign capital inflows. Simultaneously, all variables significantly influence Indonesia’s foreign exchange reserves. This study contributes empirically by integrating trade and external financing variables within a long-run ECM framework in a developing economy context.